Home Literacy Environments in Indonesia: Examining the Role of Socioeconomic Status in Family Language Practices - Ati, Veni; Indriati, Titin; Nupus, Hayati; Kiswaga, Godlove; Dicko, Abdramane; Irwansyah, Muhammad (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Literacy is understood as more than the ability to read and write, as it also involves cognitive skills shaped by social and cultural experiences and is closely linked to language acquisition. This study aims to examine how Indonesian families support literacy development at home and how socioeconomic factors influence these practices. Using Spolsky’s (2004) Family Language Policy (FLP) framework, the study applies a qualitative approach with data collected through questionnaires and interviews. The findings show that, although families generally demonstrate positive attitudes toward language use and engage in supportive literacy practices, their efforts in systematic literacy planning remain limited. In terms of socioeconomic influence, only mothers’ educational background is found to have a significant impact, particularly in shaping language-related practices and literacy support at home. Other factors, such as fathers’ education, occupation, and household income, show no strong influence on family language policy or foreign language literacy planning.